Keynesian macroeconomics without the LM curve: IS-MP-IA model and Taylor rule applied to some CESEE economies - Dushko Josheski (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Applying IS-MP-IA model and the Taylor rule, this study finds that for selected CESEE economies (Albania, Bosnia and Herzegovina, Macedonia and Serbia), lower expected inflation rate, real exchange rate appreciation, a lower world interest rate which is calculated like a federal funds rate minus inflation in US, and more world output would help to increase output of the selected economies in the sample. A lower ratio of government consumption spending to GDP would also increase the output of the selected economies. Hence, fiscal prudence is needed, and the conventional approach of real depreciation to stimulate exports and raise real output does not apply to the selected CESEE economies. When private household consumption is in the model the coefficient on government spending to nominal GDP is insignificant implying that Ricardian equivalence does hold for the selected countries. These results are robust because they are controlled in the period of four decades from 1969 to 2013. Study uses 4 decadal dummies that control for each decade.
Keywords: E52; F41; 330; IS-MP-IA; Taylor Rule